Telegram from Arthur Elrod to William F. Cody, January 26, 1960 - Arthur Elrod::::::author::: (1960)
Printed scan of a telegram from Arthur Elrod congratulating William F. Cody on an article from the 'New York Times' featuring his Eldorado ("El Dorado" [sic]) Country Club. January 26th, 1960. Text reads: "Congratulations on article appearing in today's New York Times showing El Dorado Country Club -- Arthur Elrod."